Evaluation of management in acute coronary syndrome and extent of adherence to standard treatment guidelines - Shah, Aalesh; Parikh, Nehal R.; Rana, Devang; Malhotra, Supriya; Patel, Tejas (International Journal of Basic & Clinical Pharmacology, 2022)
Background: India has the highest burden of acute coronary syndrome (ACS) in the world. This research is to evaluate prescriptions pattern and extent of adherence to American College of Cardiology (ACC)\American Heart Association (AHA) guidelines in the management of ACS with patient outcome. Methods: Case record form containing patient’s demographic, clinical profile, diagnosis, prescription drugs (with dose, duration and frequency) were noted. Pharmacotherapy was compared to ACC/AHA guidelines, to evaluate adherence, guideline adherence index (GAI-5) was used for 5 major drug groups for ACS. GAI was calculated as: number of patients using the prescribed medications/number of eligible patients multiplied by 100. Results: A total of 172 patients diagnosed with ACS. 64 (37.20%) Patients with the highest preponderance to ACS belonged to 51-60 years age group with a 4.73:1 male to female ratio. ST-elevation myocardial infarction (STEMI) (44.77%) was the most common diagnosis and an average of 14.66±4.34 drugs were prescribed. Majority of the patients opted for percutaneous coronary intervention (PCI) with or without having received fibrinolytic therapy at onset. Adherence to the ACC/AHA guidelines being 93.75% and 118 prescriptions being 100% adherent to the guidelines. A positive correlation between adherence and number of drugs was statistically significant. Conclusions: The success of evidence-based medicine (EBM) was well noted with a 0% in hospital mortality rate i.e. all of the 172 patients were discharged with therapeutic success. Despite the concept of EBM and its proven effectiveness, there is a paucity of availability of such guidelines in India, so this study, a first of its kind can serve as a starting point of generating national as well as local guidelines.